Bibliometric Analysis of Islamic Education Management - Eli Sabrifha (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2022)
The purpose of this study is to describe the concentration of topics on Islamic education management in the future in order to gain a full understanding. The google schoolar data source is used because it is considered to have the most number of articles discussing Islamic education management. As a bibliometric analysis tool, the VOSviewer software is used to show the author's network. The search was carried out on October 13, 2022 inputted with the keyword "Islamic education management". The limit of the last five years from 2017 to 2022 was chosen to reduce the number of document findings which reached 17,700. The results explain that there are still few related writers discussing the management of Islamic education. Then the authors who publish the most works are Ali Hapzi and Kasfur, they are also the longest-running writers on this topic.